2019
DOI: 10.1371/journal.pone.0226583
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils remain detrimentally active in hydroxyurea-treated patients with sickle cell disease

Abstract: Neutrophilia is a feature of sickle cell disease (SCD) that has been consistently correlated with clinical severity and has been shown to remain highly activated even at steady state. In addition to induction of fetal hemoglobin (HbF), hydroxyurea (HU) leads to reduction in neutrophil count and their adhesion properties, which contributes to the clinical efficacy of HU in SCD. Although HU reduces the frequency and severity of acute vaso-occlusive crises (VOCs) and chest syndrome, HU therapy does not abolish th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
1
13
2
Order By: Relevance
“…In comparison with healthy neutrophils, IFC competently detected changes cell membrane texture in neutrophils isolated from patients with sickle cell disease at steady state. This environment, known for its high inflammatory potential and high levels of free-circulating heme, was also directly linked with an increased potential for NETs production ( 15 ). Thus, while it does appear that NETs-associated cell membrane damage is stimulus-dependent, it might nevertheless be a useful parameter to follow up while characterizing NETosis.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with healthy neutrophils, IFC competently detected changes cell membrane texture in neutrophils isolated from patients with sickle cell disease at steady state. This environment, known for its high inflammatory potential and high levels of free-circulating heme, was also directly linked with an increased potential for NETs production ( 15 ). Thus, while it does appear that NETs-associated cell membrane damage is stimulus-dependent, it might nevertheless be a useful parameter to follow up while characterizing NETosis.…”
Section: Resultsmentioning
confidence: 99%
“…They serve as dynamic cytokine reservoirs even under healthy conditions [ 52 ]. The intravascular hemolysis of abnormal hemoglobin was discovered to initiate vascular inflammation due to the release of cytokines and, further, inflammatory mediators, thus inducing excessive NETs formation during the VOC of SCD [ 53 , 54 ]. A recent study confirmed the parallel induction of both NETs and inflammatory agents in plasma collected during VOC compared to the steady-state conditions [ 55 ].…”
Section: Vascular Occlusionsmentioning
confidence: 99%
“…demonstrated the importance of elevated plasma heme in a humanized SCD mouse model. In fact, unstimulated neutrophils isolated from SCD patients rapidly begin forming NETs compared to almost no NET formation in age-matched healthy controls, even when under treatment with hydroxyurea ( 67 ). This elevated level of heme induces arrested neutrophils to release NETs that have been associated with hypothermia and rapid death.…”
Section: Targeted Therapeutics Against Leukocyte and Platelet Activation In Vaso-occlusive Crisismentioning
confidence: 99%